PELAKSANAAN PROGRAM PEMBINAAN KEMANDIRIAN MELALUI KEGIATAN KEWIRAUSAHAAN BAGI NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS IIA MATARAM - Herliansah, Dwi Putra (Universitas Hamzanwadi, 2020)
The discussion of this research is within the scope of the implementation of one of the fostering independence of the entrepreneurship guidance program. Entrepreneurship is a creative and innovative behavior and ability so that it can be used as a basis to gain profits through a skill in the field of business, besides that entrepreneurial activities can also be used as a program for the formation of entrepreneurial behavior in prisoners. Prisoners are convicts who are undergoing the crime of missing independence at the Correctional Institution, Correctional Institutions are required to provide a forum for inmates so that prisoners can channel their talents and expertise and expertise interests. The objective of the researcher in conducting research is to find out the implementation of fostering independence and inhibiting factors or obstacles in the continuity of the process of fostering entrepreneurial independence, where each activity process has obstacles in the process of such activities such as the results of research on theindependence fostering program at the Class IIA Mataram Prison there are still obstacles such as the lack of budget, the quality and quantity of the officers themselves and the facilities and infrastructure that support the success of the self-help development program itself.Doi: 10.29408/jpek.v4i1.1977